Correlation of Cadmium Intake from Water and Biomarkers in Resident Living Around Namobintang Dumpsite - Taufik Ashar; Wirsal Hasan; Hamonangan Nainggolan; Erman Munir (Universitas Gadjah Mada, 2016)
Cadmium (Cd) is a toxic element ubiquitous in the environment and can cause kidneys damage. The aim of this study was to determine the concentration of Cd in wells water and urine of population that lived around Namobintang dumpsite, and to examine the quantitative relationship between urinary Cd and other risk factors and β2 microglobulin in urine (β2-MG-U) as a marker exposure to Cd. This study was performed in the community residence around Namobintang dumpsite. Water samples were collected from the wells around the dumpsite. The area selected was of about 1 km radius from the dumpsite. A total of eighty urine samples checked using primary data. Adult males and females aged 18-78 years old were the respondents. Study results showed that Cd levels from the wells revealed that 73 respondents (91.3%) had exposed to Cd higher than normal levels (5 µg/L). 14 urine samples (17.5%) had high Cd levels above the normal limits and 48 urine samples had high β2-MG-U levels. There was a significant correlation between the Cd levels from the wells and β2-MG-U levels (r = 0.278, p = 0.012). UCd levels had also significant correlation with β2-MG-U levels (r = 0.29, p = 0.009).